STRESS MANAGEMENT STRATEGIES FRO ELEMENTARY SCHOOL: MPLICATIONS FOR CHILD MENTAL HEALT - Corneasari, Maharani Lintang; Padang, Tito Zethaldo Rinding (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
This study explores stress management strategies for elementary school students, focusing on the mental health implications for children. The research was conducted among 5th and 6th grade students from two elementary schools in Semarang District. The collaboration between elementary school teachers and a psychiatrist aimed to address the growing concerns over the emotional and psychological well-being of young learners. The study seeks to identify effective strategies to mitigate stress among students, with a focus on preventive measures and coping techniques that can be integrated into the school environment. Data was collected through surveys, interviews, and observations to assess students' stress levels and the impact of stress on their academic performance and social relationships. Findings from this study emphasize the importance of early intervention and a supportive school environment in promoting mental health. Furthermore, the research highlights the need for a comprehensive approach involving teachers, mental health professionals, and parents in managing stress. This study contributes to the growing body of literature on childhood stress and its implications for mental health, offering practical recommendations for schools in Semarang District